Review of Drive Systems Applied in Modern Vehicles - Szántó, Attila; Mankovits, Tamás; Szíki , Gusztáv Áron (International Journal of Engineering and Management Sciences, 2020)
In this publication we review the drive systems of modern electric and hybrid vehicles. We also discuss the various types of electric motors, batteries, as well as fuel cell systems applied in them. Furthermore, as an important part of hybrid vehicles is the internal combustion engine, we review the literature about the methods used to.